1987
DOI: 10.2307/1130217
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Inertia Reduces Distractibility during Young Children's TV Viewing

Abstract: The longer a look at TV is maintained, the conditional probability that it will be further maintained rapidly increases for about 15 sec, after which it increases slowly. This increase in the conditional probability of maintaining a look is called "attentional inertia." An external audiovisual distractor stimulus was presented during 3- and 5-year-olds' TV viewing. The distractor was less effective in eliciting a head turn from the TV if it was presented after a look at the TV had been continuously maintained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
92
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(99 citation statements)
references
References 0 publications
7
92
0
Order By: Relevance
“…Thus, level of distractibility, per se, cannot be used to assess whether or not an infant is focused intently on an object because other factors, such as a high degree of motor involvement, could be operating. While this may not be an issue for older, preschool children (Anderson, Choi, & Lorch, 1987), or for any study where motor activity is constrained (Oakes & Tellinghuisen, 1994), it clearly is a factor for infants and other young organisms playing freely. Although we continue to think of infants' examining as reflecting focused visual attention and exploration, the concept of distractibility requires that we acknowledge that the motor involvement in some activities may preclude responsiveness to events outside the sphere of that activity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, level of distractibility, per se, cannot be used to assess whether or not an infant is focused intently on an object because other factors, such as a high degree of motor involvement, could be operating. While this may not be an issue for older, preschool children (Anderson, Choi, & Lorch, 1987), or for any study where motor activity is constrained (Oakes & Tellinghuisen, 1994), it clearly is a factor for infants and other young organisms playing freely. Although we continue to think of infants' examining as reflecting focused visual attention and exploration, the concept of distractibility requires that we acknowledge that the motor involvement in some activities may preclude responsiveness to events outside the sphere of that activity.…”
Section: Discussionmentioning
confidence: 99%
“…A few prior findings suggest that adding trials to a task increases the difficulty of shifting to a new response or strategy (Anderson, Choi, & Lorch, 1987). Marcovitch and Zelazo (1999), for example, found that infantsÕ perseverative searching increases with the number of successive trials in which an object was found at the first location.…”
Section: Studymentioning
confidence: 99%
“…More recently, Burns and Anderson (1993) provided similar evidence for adults across completely-unrelated boundaries between dramatic programs and commercials (however, related analyses by Hawkins, Tapper, Bruce, & Pingree, 1995, raise some questions about the interpretation of these results as a general, nonstrategic tendency). Evidence of greater engagement can be found in reduced distractibility with time (Anderson, Choi, & Lorch, 1987;Choi & Anderson, 1991). In addition, content occurring more than 15 seconds into a look is retained better than content occurring early in a look, regardless of the eventual length of the look (Burns & Anderson, 1993).…”
mentioning
confidence: 99%